2000
DOI: 10.1038/sj.bjp.0703498
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of zofenopril and lisinopril to study the role of the sulfhydryl‐group in improvement of endothelial dysfunction with ACE‐inhibitors in experimental heart failure

Abstract: 1 We evaluated the role of SH-groups in improvement of endothelial dysfunction with ACEinhibitors in experimental heart failure. To this end, we compared the vasoprotective e ect of chronic treatment with zofenopril (plus SH-group) versus lisinopril (no SH-group), or Nacetylcysteine (only SH-group) in myocardial infarcted (MI) heart failure rats. 2 After 11 weeks of treatment, aortas were obtained and studied as ring preparations for endothelium-dependent and -independent dilatation in continuous presence of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 34 publications
4
41
0
4
Order By: Relevance
“…A putative local effect of Ang-(1-7) would be in line with a previous study, 17 in which 12 days of Ang-(1-7) infusion was found to inhibit restenosis after balloon-catheter injury of carotid arteries. Interestingly, infusing Ang-(1-7) to levels obtained with ACE inhibition 6 yields similar beneficial effects, including reduction of left ventricular end-diastolic pressure, 15 preservation of aortic endothelial function, 14,18 improvement of coronary flow, 14 and reduction of myocyte hypertrophy. 19 On the other hand, differences seem to exist between Ang-(1-7) infusion and ACE inhibition.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A putative local effect of Ang-(1-7) would be in line with a previous study, 17 in which 12 days of Ang-(1-7) infusion was found to inhibit restenosis after balloon-catheter injury of carotid arteries. Interestingly, infusing Ang-(1-7) to levels obtained with ACE inhibition 6 yields similar beneficial effects, including reduction of left ventricular end-diastolic pressure, 15 preservation of aortic endothelial function, 14,18 improvement of coronary flow, 14 and reduction of myocyte hypertrophy. 19 On the other hand, differences seem to exist between Ang-(1-7) infusion and ACE inhibition.…”
Section: Discussionmentioning
confidence: 87%
“…14 To examine the effects of Ang-(1-7) treatment on this aspect of cardiac failure, we investigated endothelium-dependent relaxation in isolated aortic rings. Phenylephrine elicited similar contractile responses in all 3 groups (data not shown).…”
Section: Endothelial Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area under each individual curve (AUC) was determined (Sigma Plot; SPSS Inc., Chicago, IL) and expressed in arbitrary units. The AUC was used to present total (individual) ACh dilation, and for subsequent analysis of differences in ACh dilation with and without indomethacin (Buikema et al, 2000). Data are expressed as mean Ϯ S.E.M.…”
Section: Methodsmentioning
confidence: 99%
“…Thiosulfate is used as a treatment for calcifylaxis in patients with end-stage renal disease (111) and has been described as a protective agent in hypertensive heart and renal disease in rats (109,157). Sulfhydrylated ACE inhibitors, such as zofenopril and captopril, show additional beneficial effects in different trials (158). Recently, it was demonstrated that the beneficial effects of sulfhydrylated ACE inhibitors are explained by H 2 S release (159).…”
Section: Future Perspectives and Treatment Optionsmentioning
confidence: 99%